SAT0555 Transmigration and Mobility of Rheumatoid Arthritis Synovial Fibroblasts is Dependent on Distinct Interaction Processes with Endothelial Cells. (10th June 2014) - Neumann, E.; Zimmermann, B.; Köppert, S.; Rehart, S.; Müller-Ladner, U.
Abstract : Background: Synovial fibroblasts (SF) from patients with rheumatoid arthritis (RA) are involved in cartilage destruction. The behavior of RASF to migrate over long distances could be demonstrated in the SCID mouse model of RA: RASF migrate from the primary implantation site through the vasculature to distant implanted cartilage. For extravasation of RASF, up-regulation of adhesion molecules and binding of RASF to endothelial cells (EC) is crucial. Moreover, pro-angiogenic effects of RASF are known, which also require interaction with the vasculature. Objectives: To elucidate the molecules involved in the binding process of RASF to EC. Methods: Synovium of RA and osteoarthritis (OA) patients were double-stained for CD15s (E-selectin ligand) and vimentin (fibroblast marker). Serum stimulated RA- and OASF were stained for CD15s. Adhesion under dynamic conditions was analyzed by a laminar flow assay using RA- and OASF. Mobile SF, adherent and tethering on EC were quantified. The capillary slides were coated with E- or P-selectin (E-/P-S) or coated with 10ng/ml TNF-activated (aHUVEC) or untreated HUVEC. Static adhesion was analyzed with a cell-to-cell binding assay. SF were stained with Calcein-AM, resuspended in RPMI or DMEM, and incubated for 15 min on a monolayer of aHUVEC or HUVEC. Adherent SF were then quantified. Results: The E-S ligand CD15s was expressed in all RA tissues (n=12) but only in 1/7 OA tissues. In 67% of the RA synovia, CD15s was co-localized with vimentin. Double stained cells were mainly located in the sublining (50%) but also inside vessels (33%) or both compartments (33%). CD15s expression in cultured SF was induced by RA serum in 80% of RASF (n=5) in contrast to 33% of OASF (n=3). Healthy serum did not induce CD15s. Adhesion of RASF (n=4) to E-S-coated capillaries was significantly higher than to P-S at all flow rates (e.g. 18.4 ml/h: E-S=15.3±2.5 vs. P-S=1.5±1.5; 30.5 ml/h: E-S=9.3±1.8 vs. P-S=0.3±0.3); Adhesion of RASF to E-S coating was significantly stronger than of OASF (n=3; e.g. 18.4 ml/h: E-S=2.1±0.2). Adhesion of RASF (n=3) to aHUVEC was also significantly increased at 18.4 ml/h (9.7±1.3) compared to OASF (2.1±0.4). In the static assay (n=3) a significantly increased adhesion was visible with RASF in RPMI on aHUVEC (122.1±10.3). Adhesion of RASF to HUVEC in RPMI (78.2±7.3) vs. aHUVEC in DMEM (77.1±6.5) was similar. Adhesion of RASF to HUVEC in DMEM (58.7±5.9) showed the lowest amount of adherent RASF. OASF showed a less adhesion compared to RASF (aHUVEC in RPMI: 55.0±3.1; HUVEC in RPMI: 47.2±5.1; aHUVEC in DMEM: 62.2±2.9; HUVEC in DMEM: 50.3±3.4). Conclusions: The experiments revealed an increased adhesion behavior of RASF as compared to OASF. This effect was also visible in the dynamic adhesion assay using EC and most likely based on specific CD15 expression and subsequent interaction with endothelial cells. Thus, induction of CD15s and the ability to interact with EC could represent a key mechanism of RASF by which they migrate through and leave the vascular system at specific sites. Beside selectins, other adhesion molecules which are known to be increased in RASF are likely to participate in this initial interaction of SF with EC. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2471